Evaluation of alkane indexes for quantifying organic source from end member mixing experiments based on soil and algae. (December 2019) - Lee, Dong-Hun; Choi, Hye-Bin; Won, Eun-Ji; Derrien, Morgane; Hur, Jin; Shin, Kyung-Hoon
Highlights: Binary mixtures of soil and algae were used to validate the end-member mixing analysis for n -alkane indexes. Typical n -alkane indexes showed some limitations for quantitative source tracking. δ 13 C value of C25 alkane is suggested as a viable organic source tracking indicator. Abstract: The identification for the sources of organic matters (OMs) is necessary to better understand biogeochemical cycling of carbon in aquatic environments. Hence, we intend to evaluate quantitative contributions of OM sources by using typical n -alkane indexes. In this regard, the end-member mixing experiment was designed as an example of theoretical system, which was physically mixed by two contrasting OM sources (e.g. soil and algae). Two sources showed distinct patterns with the long-chain alkanes (e.g., mainly C25, C27, C29, C31 and C33 ) for soil, but mid-chain alkanes (e.g., mainly C19, C21, C23 and C25 ) for algae. However, typical n -alkane indexes such as average chain length (ACL), carbon preference index (CPI), and aquatic plants % (Pmar-aq ), except for terrestrial/aquatic ratio (TAR), were not well reflected for different proportions of mixed OM sources, indicating the overestimated contribution of soil sources. With respect to source tracking capability of n -alkane indexes, the calculated regression slope indicated non-linear relationships (R 2 = 0.52–0.67) in ACL, CPI, and Pmar-aq, and linear relationships (R 2 = 0.86) in TAR, while the most precise capability was found for carbon isotopic compositions (δ 13 C) of C25 alkane (linear relationships; R 2 = 0.97) calculated from the isotope mixing model. Thus, the present study suggests that a binary mixing model of C25 alkanes concentrations combined with their isotopic values should be a promising tool for quantifying each contribution of autochthonous and/or allochthonous OM in natural aquatic environments.